Synthesis and spectral investigations of 2,5,7-triaryl-5H-[1,3,4] thiadiazolo[3,2-a]pyrimidin-6[7H]-ones - Koparir, Metin; Cansiz, Ahmet; Çetin, Ahmet (Chemical Publishing Co., 2005)
A general and convenient route for the synthesis of 5-(aryl)-[1,3,4] thiadiazol-2-ylamines (2a-d), Schiff bases of thiadiazoles (3a-p) and 2,5,7-triaryl-5H-[1,3,4]thiadiazolo[3,2-a]pyrimidin-6[7H]-one (4a-p) is reported. The characterizations of these compounds were obtained by elemental analyses, IR, 13C and 1H NMR techniques.
Keywords: 2,5,7-Triaryl-5H-[1,3,4]-thiadiazolo[3,2-a]pyrimidin- 6[7H]-ones; Spectral; Synthesis